(untitled) (Fiep Bulletin - online, 2012)
Leisure presents itself increasingly as an essential component to the life of the contemporary individual. Among the benefits that practice provides, are the personal and social development, fun and rest. This study aimed to identify potential public and private leisure in the city of Altamira / Para, checking the status of conservation and the use of these, and discuss public policies for this sector. The methodology used was a quantitative research, exploratory and descriptive, presenting the results graphically. We used a literature search of secondary sources of the main theorists who deal with the theme, followed by insertion of the researchers on the spot by recording space and equipment that sill the cultural content of leisure. This research was based on authors such as Bruhns, (1993), Dumazedier, (1976), Marcellino (1996a, 1996b, 2001, 2007) Camargo (1986), Angelo (2007) Gomes (2005), Melo and Alves Junior ( 2003), Mascarenhas (2001) and Requixa (1980), among others. There was a poor distribution of these spaces, because the vast majority concentrated in the central regions of the city as Premem neighborhoods (14%) and Centro (9%), while the prevalence in the peripheral regions were observed fields and floodplains unpaved, primarily used for soccer practice, as the neighborhoods Liberdade (2%) and Ibiza (5%). It was noticed that the vast majority of areas and equipment are vandalized, which shows an inefficiency of public policies for this sector. It is noteworthy that the population plays a key role in order to provide spaces for the practice of leisure in the various neighborhoods. The main avenues present themselves as places where demonstrations of leisure activities are evident. Thus, the areas and equipment should be better distributed to democratize the practice provided by law, because leisure is an important factor to promote quality of life.